2019
DOI: 10.1002/pssb.201900619
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction of the Low‐Temperature Ferromagnetic Semiconducting 2D SiN Monolayer

Abstract: Since the discovery of graphene, 2D materials have captured the minds of scientists because of their attractive and unique electronic properties. In particular, magnetic 2D materials have become a subject of extensive discussions today. Using density functional theory calculations, it is shown that 2D SiN sheet (built out of nonmetallic main group atoms) is a ferromagnetic semiconducting material with a magnetic moment 1 μB per unit cell and an indirect bandgap of 1.55 eV. Calculated phonon spectrum and conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…The HSE band structure of FM monolayer AlN is shown in Figure 7A, indicating that it is a 2D FM semiconductor with an indirect band gap of 1.556 eV, consistent with previous work [53]. We considered four possible magnetic configurations, including FM, AFM1, AFM2, and AFM3 configurations (Figures 8A-D).…”
Section: Monolayer Sin: the Extreme Doping Limitsupporting
confidence: 78%
“…The HSE band structure of FM monolayer AlN is shown in Figure 7A, indicating that it is a 2D FM semiconductor with an indirect band gap of 1.556 eV, consistent with previous work [53]. We considered four possible magnetic configurations, including FM, AFM1, AFM2, and AFM3 configurations (Figures 8A-D).…”
Section: Monolayer Sin: the Extreme Doping Limitsupporting
confidence: 78%
“…AdNDP works within the concept of electron density overlapping. AdNDP, particularly SSAdNDP, was successfully applied as a bonding decoder to many one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D) systems including those with aromatic properties. Both NBO and AdNDP use the concept of occupation numbers (ONs), which represent the amount of electron density localized on a multicenter bond. The closer these values to 2.0, the more reliable a bonding picture is.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the chemical bonding pattern of the 2D‐B 4 P 2 sheet, the solid‐state adaptive natural density partitioning (SSAdNDP) algorithm was used . Previously it was shown that SSAdNDP is a powerful tool for analyzing chemical bonding in two‐dimensional periodic systems . A plane wave (PW) calculation was performed using 450 eV energy cut off with convergence threshold 10 −6 eV for total energy.…”
Section: Methodsmentioning
confidence: 99%